2020
DOI: 10.1111/1365-2435.13677
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungi and fine root biomass mediate drought‐induced reductions in soil respiration

Abstract: 1. Climate change has increased the frequency and intensity of droughts, with potential impacts on carbon (C) release from soil (i.e. soil respiration, Rs). Although numerous studies have investigated drought-induced changes in Rs, how roots and the soil microbial community regulate responses of Rs to drought remains unclear. 2. We conducted a 4-year field experiment (2014-2017) with three treatments (i.e. 70% rainfall reduction, control and ambient) in a subtropical forest to examine effects of drought on Rs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 45 publications
1
22
3
Order By: Relevance
“…According to the optimal partitioning theory (Bloom et al, 1985), plants should allocate more C to root growth from aboveground parts to reduce water limitation (Fuchslueger et al, 2014). However, many eld throughfall exclusion experiments of forests have shown that ne root biomass did not always support this theory, including increase (Zhou et al, 2020), decrease (Moser et al, 2014), or little change during the rst four years in this study (Lu et al, 2017), indicating that the responses of ne root to water de cit depends on intensity and duration of drought. In our system, we argued that mature trees increased belowground C allocation to adapt to the long-term drought, resulting in the higher AR.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…According to the optimal partitioning theory (Bloom et al, 1985), plants should allocate more C to root growth from aboveground parts to reduce water limitation (Fuchslueger et al, 2014). However, many eld throughfall exclusion experiments of forests have shown that ne root biomass did not always support this theory, including increase (Zhou et al, 2020), decrease (Moser et al, 2014), or little change during the rst four years in this study (Lu et al, 2017), indicating that the responses of ne root to water de cit depends on intensity and duration of drought. In our system, we argued that mature trees increased belowground C allocation to adapt to the long-term drought, resulting in the higher AR.…”
Section: Discussioncontrasting
confidence: 58%
“…It has been shown that drought reduced AR, and thus SR, but had no effect on HR in a dry temperate forest (Hinko-Najera et al, 2015). Another study in a subtropical forest found drought decreased both AR and HR, and hence SR (Zhou et al, 2020). A previous study in a warmtemperate oak forest also suggested that drought increased AR but not HR, and therefore SR at a small scale (e.g., 4 m × 4 m roof) throughfall reduction (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…According to the optimal partitioning theory (Bloom et al 1985), plants should allocate more C to root growth from aboveground parts to reduce water limitation (Fuchslueger et al 2014). However, many field throughfall exclusion experiments of forests have shown that fine root biomass did not always support this theory, including increase (Zhou et al 2020), decrease (Moser et al 2014), or little change during the first 4 years in this study (Lu et al 2017), indicating that the responses of fine root to water deficit depends on intensity and duration of drought. In our system, we argued that mature trees increased belowground C allocation to adapt to the longterm drought, resulting in the higher AR.…”
Section: Discussioncontrasting
confidence: 82%
“…Another study in a subtropical forest found that drought decreased both AR and HR, resulting in 17% reduction in SR (Zhou et al 2020). However, a previous study in a warm-temperate oak forest suggested that drought increased SR by 26.7% at a small scale (e.g., 4 m × 4 m roof) throughfall reduction, which was mainly attributed to the increase in AR (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Nevertheless, numerous studies have shown that greater plant biomass does not always lead to increases in the biomass or abundance of soil micro-organisms. Neutral and negative results have also been reported (Li et al 2021;Zhou et al 2020).…”
Section: Introductionmentioning
confidence: 83%